Preliminary estimation of fouling organisms associated with the pearl oyster Pinctada radiata in the natural habitat of the Egyptian Mediterranean Sea - ABDELSALAM, KHALED M.; ELEBIARY, NOHA H. (Mediterranean Marine Science, 2023)
In the summer of 2021, marine fouling organisms associated with the pearl oyster Pinctada radiata in the natural habitat of Miyami area, Alexandria city, were surveyed, where samples were collected by scuba diving. Eighteen shells of variable sizes were collected to investigate the fouling community’s biodiversity that settled on each shell. A total of 1674 organisms representing 106 fouling taxa were identified, weighing a cumulative wet weight of 147.98 g. The community composition consists of 52 taxa of Polychaeta, 19 species of Arthropods, 18 species of Mollusks, 5 species of Bryozoans, 4 species of Chordata, 2 species of Rhodophytes, Anthozoans, and Echinoderms, and one species for Sponge, and Platyhelminth. Species diversity, abundance, and total wet weight were variable among the eighteen studied shells, with higher recorded values on larger shells. The two barnacles (Balanus trigonus and Perforatus perforatus) were the most dominant species, followed by the Syllidae polychaete Haplosyllis spongicola, then the alien mytilid bivalve Brachidontes pharaonis, and the Dorvilleidae alien polychaete (Dorvillea similis). A comparison with other similar studies in the Mediterranean Sea was conducted. Before performing manipulative studies on how biofouling communities might affect aquaculture productivity, it is first necessary to ascertain the composition of these organisms within the desired aquaculture locations.